Evaluation and development of maize germplasm for resistance to spotted stem borer - Kanta, U.=700 1 Dhillon, B.S.; Sekhon, S.S.
Sumario (En)
Ilus.; 42 ref.
Keywords: ZEA MAYS; GERMOPLASMA; RESISTENCIA A LAS PLAGAS; INSECTOS DAÑINOS DEL TALLO; INSTITUCIONES DE INVESTIGACION; CONTROL DE PLAGAS; EVALUACION